Rat Cavernous Nerve Reconstruction with CD133+Cells Derived from Human Bone Marrow. (1st May 2014) - Miyamoto, Katsutoshi; Inoue, Shogo; Kobayashi, Kanao; Kajiwara, Mitsuru; Teishima, Jun; Matsubara, Akio
Abstract: Introduction: Erectile dysfunction remains a major complication after surgery of pelvic organs, especially after radical prostatectomy. Aim: The aim of this study was to assess the effect of endothelial progenitor cells on the regeneration of cavernous nerves in a rat injury model. Methods: A 2 mm length of the right and left cavernous nerves of 8 week old male nude rats were excised. Alginate gel sponge sheets supplemented with 1 × 10 4 CD133 + cells derived from human bone marrow were then placed over the gaps on both sides (CD group). The same experiments were performed on sham operated rats (SH group), rats with only the nerve excision (EX group), and rats with alginate gel sheets placed on the injured nerves (AL group). Main Outcome Measures: Immunofluorescence staining and molecular evaluation were performed 4 days later. Functional and histological evaluations were performed 12 weeks later. Results: The intracavernous pressure elicited by electrical stimulation and the neuronal nitric oxide synthase positive area in surrounding tissues of the prostate was significantly greater in the CD group. Immunofluorescence microscopy showed that CD133 + cells were assimilated as vascular endothelial cells, and the real time polymerase chain reaction showed upregulation of nerve growth factor and vascular endothelial growth factor in the alginate gel sponge sheets of the CD group. Conclusions: Transplantation of CD133 + cells accelerated the functional and histological recovery in this cavernous nerve injury model, and the recovery mechanism is thought to be angiogenesis and upregulation of growth factors. CD133 + cells could be an optional treatment for cavernous nerve injury after prostatectomy in clinical settings.